Evaluation and use of a monitoring method to estimate Atlantic salmon spawning run - Pedersen, Sonja Lydia Kimo (UiT Norges arktiske universitet, 2021)
ARIS sonar and Timespace video cameras were used to estimate spawning run and migration pattern of Atlantic salmon in Máskejohka, a tributary belonging to the River Tana. Máskejohka has not been monitored before and needs more detailed information about the stock size and its migration pattern, after several years with declining Atlantic salmon catch. Data for the first weeks of the migration period was hampered by an extreme spring flood, and the total sonar data coverage for the period (31.05.2020-15.09.2020) was 78%. Fish ≥ 45 cm were divided into the following length classes, based on measurements from the sonar data: 45-55 cm, 55-67 cm, 67-89 cm and > 89 cm. Only fish ≥ 45 cm was included, due to minimum Atlantic salmon size. Fish species were subjectively identified with sonar data based on size and behavior before confirming or refuting species with video recordings. Using video-identified species, the probability of a target being an Atlantic salmon was estimated by binomial regression using length as predictor. Estimation of total Atlantic salmon run was then completed using the regression model to estimate the proportion of Atlantic salmon among the targets observed on video. For the period with missing data, the potential run was estimated based on development from week to week from catch statistics from the previous years. Results from the sonar and video analyses were compared to catch statistics from Máskejohka to calculate the size of the spawning stock. The total number of fish registered by the sonar was 1810, 1270 upstream and 539 downstream. A total of 110 Atlantic salmon 75 grayling, 16 trout, 2 whitefish, 2 pike and one pink salmon during the period of 16 days (30.07.2020-14.08.2020) were observed on the video recordings. Grayling dominated the smallest size group between 45-55 cm, while the size group 55-67 cm was dominated by Atlantic salmon. Trout was present in both the smallest length classes. The larger size classes of 67-89 cm and > 89 cm contained only Atlantic salmon. Atlantic ...